2021
DOI: 10.1109/jphot.2021.3057666
|View full text |Cite
|
Sign up to set email alerts
|

High Sensitivity and High Stability Dual Fabry-Perot Interferometric Fiber-Optic Acoustic Sensor Based on Sandwich-Structure Composite Diaphragm

Abstract: A dual Fabry-Perot (FP) interferometric fiber-optic acoustic sensor based on sandwich-structure composite diaphragm is proposed, where fixed phase difference is generated by two FP interferometers (FPIs) with different cavity length. An ellipse fitting differential cross multiplication (EF-DCM) interrogation process is applied for phase demodulation to overcome drawbacks of quadrature point based intensity demodulation, such as temperature drifting, optical power jitter and limited dynamic range. Besides, bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…For instance, while large-sized piezoelectric acoustic sensors possess a high sensitivity and signal-to-noise ratio, it is disadvantageous to sensor miniaturization that is urgently desired in practical applications, and the low resonant frequency of membranes result in a narrow frequency response of sensors. Furthermore, in order to adapt to the expansion of the acoustic detection field and the application requirements of the harsh environment, fiber-optic acoustic sensors (FOASs) with the advantages of a high sensitivity [6][7][8][9], immunity to electromagnetic interference [10][11][12], high temperature resistance and miniaturization [13,14] have been widely studied and applied in the fields of national defense security [15,16], medical diagnosis [17][18][19] and non-destructive testing [20,21]. At present, optical fiber [8] and membrane [22][23][24][25][26] are the most commonly used sound-sensitive element.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, while large-sized piezoelectric acoustic sensors possess a high sensitivity and signal-to-noise ratio, it is disadvantageous to sensor miniaturization that is urgently desired in practical applications, and the low resonant frequency of membranes result in a narrow frequency response of sensors. Furthermore, in order to adapt to the expansion of the acoustic detection field and the application requirements of the harsh environment, fiber-optic acoustic sensors (FOASs) with the advantages of a high sensitivity [6][7][8][9], immunity to electromagnetic interference [10][11][12], high temperature resistance and miniaturization [13,14] have been widely studied and applied in the fields of national defense security [15,16], medical diagnosis [17][18][19] and non-destructive testing [20,21]. At present, optical fiber [8] and membrane [22][23][24][25][26] are the most commonly used sound-sensitive element.…”
Section: Introductionmentioning
confidence: 99%
“…Authors in [2] proposed an optical scanning system wherein they suggested changing the intensity distribution from the center and the edge of the beam using a prism. Authors in [3] used a double Fabry Perot interferometer acoustic sensor to get rid of temperature drifting. Authors in [4] tried a number of alterations using silicone converters which helped increase the top-limit excitation power ranging from 60 to 180Wcm.…”
Section: Introductionmentioning
confidence: 99%
“…1. Quadrature signal acquisition: The methods to obtain two quadrature signals mainly include the phase generated carrier (PGC) method [19][20][21][22], multiwavelength method [23][24][25], construction of quadrature F-P cavity method [26][27][28][29], etc. The PGC method is susceptible to the effects of external factors such as drift of mixing signal amplitude and change of phase modulation amplitude.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the traditional PGC method is not suitable for short cavity interferometers, as with most monochromatic sources it is not possible to provide sufficient modulation depth due to the structural characteristics of short cavity interferometers. The multiwavelength approach requires optical filters or multiple light sources of different wavelengths, which complicates the sensing system and prevents the detection of high frequency signals due to the limitations of the spectrometer scanning speed [28]. In contrast, the method to obtain the quadrature signals by constructing a quadrature F-P cavity structure is simple, easy, and inexpensive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation